ANTI-VIRAL EFFECT OF HERBAL MEDICINE KOREAN TRADITIONAL CYNANCHUM PANICULATUM (BGE.) KITAG EXTRACTS - Kim, Woong; Oh, Tae-Seok; Park, Youn-Jin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Pestiviruses in general, and Bovine Viral Diarrhea (BVD) in particular, present several potential targets for directed antiviral therapy. Material and Methods: The antiviral effect of Cynanchum paniculatum (Bge.) Kitag (Dog strangling vine: DS) extract on the bovine viral diarrhea (BVD) virus was tested. First, a cytotoxicity test in MDBK (Madin-Darby bovine kidney) cells was done with all organic extract concentrations. Results: The cytotoxic concentration CC50 for the ethyl acetate (EA) extracts was 18.2 ug/ml. In the tissue culture, infectious dose (TCID50) assay, the BVD virus decreased when treated with 18.2 ug/ml of the ethyl acetate extracts. Conclusion: Ethyl acetate extracts and fractions of the DS extract could be used as a potential antiviral for BVD.